IGV Optimization for a Large Axial Flow Fan Based on MRGP Model and Sobol’ Method - Zhou, Shuiqing; Hu, Yinjie; Lu, Laifa; Yang, Ke; Gao, Zengliang (Frontiers in Energy Research, 2022)
Large axial flow fans with front guide vanes have been widely used in building ventilation systems because of their high efficiency, large flow, high pressure, and other advantages. The front guide vane deflects the air flow in front of the fan impeller to accelerate the airflow and change the fan pressure. The rotor-stator interaction between the front guide vane and the impeller is particularly important for the aerodynamic performance and noise of the fan. Therefore, parametric design has been carried out on the front guide vane of an axial flow fan. Based on numerical simulation analysis, the MRGP approximate model was established to optimize the front guide vane structure, and the Sobol’ method is employed for sensitivity analysis. The best model was selected for proofing analysis, and the experimental and numerical simulation results show that after optimization, the total pressure of the model increases by 144.4 Pa, and the noise decreases by 7.2 dB. These results verify that the multi-objective optimization design method combining the MRGP approximate model and the Sobol’ method demonstrates high credibility and provides a key design direction for the design optimization of large axial flow fans.